Resistance induction with silicon in Hass avocado plants inoculated with Phytophthora cinnamomi Rands (2023)
Root rot caused by Phytophthora cinnamomi Rands, is one of the main factors that limits avocado production worldwide; silicon as a defense inducer seems to be a viable strategy to integrate into the management of this disease. Hereby, the present study evaluated the induction of resistance with silicon in Hass avocado plants inoculated with P. cinnamomi, as a possible alternative to conventional agrochemical management. A potassium silicate solution (10 mL, 0.2 M expressed as SiO2) was applied by irrigation, for ten days before inoculation with P. cinnamomi in Hass avocado plants. Leaf samples were taken at 3, 24, 144, and 312 h after inoculation with the pathogen. Peroxidase (POD) and polyphenol oxidase (PPO) enzymes had their highest activity 3 h after pathogen inoculation (p < .05). There was a decrease in the activity of the enzyme phenylalanine ammonialyase (PAL), in the content of total phenols, and the inhibition capacity of the DPPH● radical, between 3 h and 24 h in the plants with the inducer and inoculated with P. cinnamomi (p < .05). The results suggest a beneficial effect of silicon as a defense inducer in Hass avocado plants, manifested in the activation of enzymatic pathways related to the regulation of oxidative stress and the synthesis of structural components. Therefore, the application of silicon as a defense inducer emerges as a strategy to include in the integrated management of the disease caused by P. cinnamomi in Hass avocado